Liability in Autonomous Vehicle Accidents Liability in Autonomous - Pinter, Krisztian; Szalay, Zsolt; Vida, Gabor (Communications - Scientific letters of the University of Zilina, 2017)
Nowadays, due to the constant change in the society’s expectations regarding transportation, the main area of automotive development is the implementation of autonomous vehicle control functions. While with the gradual introducing and spreading of autonomous functions-even based on the previous experience-the decrease of the number of traffic accidents is expectable, parallel we have to prepare the emergence for the new types of accidents, in which autonomous vehicles will be involved. Needs of follow-up examination and reconstruction of such type accidents makes necessary the general use of the event/accident data recorders in road vehicles and application of the new methods and tools in accident reconstruction and examination of causes of accidents. Examining a road accident it is necessary to investigate the liability issues, as well, what requires new approaches and developing of a uniform practice.